Rough sets, fuzzy sets, data mining, and granular computing : 15th International Conference, RSFDGrC 2015, Tianjin, China, November 20-23, 2015, proceedings /: 15th International Conference, RSFDGrC 2015, Tianjin, China, November 20-23, 2015, proceedings. (2015) - Unknown
No abstract available